Filsafat Bahasa Menurut Al-Farabi: Pengertian dan Implikasi Kaidah Bahasa Arab dalam menerjemahkan ”The Categories” karya Aristoteles - Muhammad Kusuma Wardhana (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2024)
This study focuses on the introduction of Philosophy of Language from Al-Farabi's perspective. Considered as the mouthpiece of the Greek philosophical tradition, Al-Farabi succeeded in creating a synthesis of philosophical knowledge between the thoughts of Plato and Aristotle. The approach used is Linguistics, which will discuss the dynamics of premises originating from grammar developed by Al-Farabi after studying with Ibn Siraj and obtaining the title of `Second Teacher` after studying the Alexandrian school of knowledge. The findings of the problems that will be studied in this study include: (1) critical analysis of the controversy over Al-Farabi's scientific transmission; (2) al-Farabi's views on the philosophy of language; (3) Implications of al-Farabi's thoughts in translating `The Categories` by Aristotle in the context of Arabic language rules.